Electrical heating element - O'CONNOR JASON DANIEL HAROLD (2013)
An electrical device includes a compound material. The compound material includes a mixture of an electrically conductive material and an electrically insulative material. The conductive material is aligned within the compound material, such that the resistivity of the compound material in a first direction is different from the resistivity of the compound material in a second direction perpendicular to the first direction.